The expanding role of GLP-1 receptor agonists: a narrative review of current evidence and future directions - Areesha Moiz; Kristian B. Filion; Michael A. Tsoukas; Oriana H.Y. Yu; Tricia M. Peters; Mark J. Eisenberg (EClinicalMedicine, 2025)
Summary: Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have transformed obesity management, offering substantial weight loss and metabolic benefits. This review examines their expanding role, evaluating efficacy compared to alternative treatments, emerging indications, ongoing challenges, and future directions. Beyond obesity and type 2 diabetes, the therapeutic potential of GLP-1 RAs extends to a range of conditions such as cardiovascular disease, liver disease, neurodegenerative disease, and substance abuse disorders. While early concerns regarding pancreatic and thyroid cancer have been largely attenuated by recent evidence, issues such as gallbladder and biliary disorders, psychiatric safety, and perioperative aspiration risk require ongoing investigation. Additionally, observations of weight regain after treatment discontinuation and reductions in lean mass highlight the need for long-term, individualized strategies to sustain clinical benefits. The high cost and limited access to these medications raise critical policy and equity challenges. Future research must address these gaps, focusing on long-term safety, optimizing combination approaches, and evaluating the broader clinical and economic implications of widespread GLP-1 RA use. Funding: K.B.F. is supported by a William Dawson Scholar award from McGill University. T.M.P. is a Fond de Recherche du Québec-Santé (FRQS) research scholar. M.J.E. holds a James McGill Professor award from McGill University. The funding sources had no involvement in the conduct of this study, interpretation of results, or the preparation of this manuscript for publication.